1992
DOI: 10.1038/356713a0
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant regulation of ras proteins in malignant tumour cells from type 1 neurofibromatosis patients

Abstract: Defects in the NF1 gene have been implicated in the inherited disorder neurofibromatosis type 1, which is characterized by several developmental abnormalities including an increased frequency of benign and malignant tumours of neural crest origin (neurofibromas and neurofibrosarcomas respectively). The NF1 gene encodes a ubiquitous protein homologous to p120GAP, the GTPase-activating protein (GAP) for the products of the ras protooncogenes. When expressed in non-mammalian systems, the region of the NF1 gene ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
343
0
7

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 610 publications
(369 citation statements)
references
References 19 publications
19
343
0
7
Order By: Relevance
“…In support of this mechanism, several studies have shown that neuro®bromin suppresses cell growth by inhibiting p21-ras activity in some cell types. These results are consistent with the notion that the tumor suppressor function of neurofibromin is related to its ability to operate as a GAP molecule (Basu et al, 1992;DeClue et al, 1992;Bollag et al, 1996;Largaespada et al, 1996). However, little is known about the function of neuro®bromin in astrocytes relevant to the development of astrocytomas in individuals a ected with NF1.…”
Section: Introductionsupporting
confidence: 88%
“…In support of this mechanism, several studies have shown that neuro®bromin suppresses cell growth by inhibiting p21-ras activity in some cell types. These results are consistent with the notion that the tumor suppressor function of neurofibromin is related to its ability to operate as a GAP molecule (Basu et al, 1992;DeClue et al, 1992;Bollag et al, 1996;Largaespada et al, 1996). However, little is known about the function of neuro®bromin in astrocytes relevant to the development of astrocytomas in individuals a ected with NF1.…”
Section: Introductionsupporting
confidence: 88%
“…This hypothesis has been formally proven by analysing the consequences of inactivating the NF1 tumor suppressor, the gene responsible for the familial cancer syndrome neurofibromatosis type I (NF1) (Courtois-Cox et al, 2006). NF1 encodes a RasGAP protein, and its inactivation has been shown to cause an acute activation of (endogenous) Ras and Ras effector pathways (Basu et al, 1992;DeClue et al, 1992). Similar to MEFs expressing a single activated K-ras allele, inactivation of NF1 via shRNA constructs results in the immortalization of this cell type (Courtois-Cox et al, 2006).…”
Section: Does Signal Intensity or Cell Type Matter?mentioning
confidence: 99%
“…Sequence analysis of the predicted NF1 protein sequence revealed that it contains a small domain with striking similarity to the catalytic segment of a family of proteins termed GTPase activating proteins. Neurofibromin was subsequently shown to be a Ras-GTPase activating protein, accelerating the conversion of active GTPbound Ras to inactive GDP-bound Ras (Ballester et al, 1990), such that loss of neurofibromin expression results in increased Ras activity and increased Ras-driven cell proliferation (Basu et al, 1992; DeClue et al, 1992).…”
Section: Susceptible Cell Typementioning
confidence: 99%